Hydrothermal Synthesis and Crystal Structure of a Novel 3D Heteronuclear Cerium and Silver Coordination Compound - WANG, CHONG-CHEN (Asian Journal of Chemistry, 2010)
The coordination compound Ce4Ag2(bpdc)4(SO4)3(H2O)6·H2O, where bpdc is 2,2'-bipyridine-4,4'-dicarboxylic acid, has been synthesized and its crystal structure was determined by X-ray diffraction. Crystal data: orthorhombic, space group Ama2, a = 26.990 (3) Å, b = 33.060 (3) Å, c = 6.9250(10) Å, V = 6179.1(12) Å3, Mr = 2159.26, F(000) = 4144, Z = 4, Dc = 2.321 Mg/m3, μ = 3.715 mm-1. The final R1 = 0.1468 and wR2 = 0.3188 for 4553 observed reflections (I>2σ(I)). Silver(I) ion is coordinated by nitrogen atoms on the pyridine rings via chelating mode, showing the distorted tetrahedron geometry. The coordination polyhedron around Ce(1) is 8-coordinated dodecahedron mo de, while the local geometry around Ce(2) is 8-coordinated bicapped trigonal prism. The title compound is in 3-dimensional supramolecular state.